The Study of Political Movement and Election Behavior in the 2023 Members of the Parliament Election in Chonburi Province - Tantrajin, Patcharapa (Thammasat Journal, 2025)
The research article has three research objectives; 1) to study, analyze, and compare the political atmosphere of the 2023 Members of the Parliament election with the past election; 2) to study the movement and political behavior of important actors who are the pollical sector, the public sector, the role of the Election Commission, relevant governmental agencies, and the role of other sectors who acted as watchdog agencies in the election and; 3) to analyze the movement as well as political and election behaviors that have an effect on the election and democratic development in the area. The research uses a qualitative methodology. The study found differences from the 2019 election. The political context at the national level has been changed, along with changes in the political and economic contexts within Chonburi. Regarding people’s election behavior, voter turnout was 77.80%. Voters made their decision by considering party policies. The Political behavior of citizens in Chonburi shows increased awareness that their rights, freedoms, and votes can be used to bring about change and realize democracy, using the election as a means of reflecting the voice of the people to the authorities at both local and national levels. The general election in Chonburi showed democratic development at the grassroots level. However, the structure at the upper level. has not reflected the political will of the citizens who turned out to vote.